Quercus trungkhanhensis (Fagaceae), a New Species from Cao Vit Gibbon Conservation Area, Cao Bang Province, northeastern Vietnam - Hoàng, Thị Bình (2023)
A new species, Quercus trungkhanhensis Binh & Ngoc (Fagaceae), from Cao Vit Gibbon Conservation Area, northeastern Vietnam is described. It is morphologically similar to Q. engleriana Seemen and Q. marlipoensis Hu & Cheng in having scaly cupules and in the shape, texture and glabrescence of the leaves, but distinguished from the former particularly by the size and morphology of the fruits (acorns and cupules) and the latter by smaller leaves with fewer lateral veins. Quercus trungkhanhensis is also similar to Q. franchetii Skan in fruit morphology, but differs in having glabrescent leaves.